Cerebellar abscess secondary to extradural internal protuberance epidermal cyst - Marleen; Syafrizal Abubakar; Achmad Jana Maulana; Michael Norman Jusman (Indoscholar, 2019)
An Intracranial epidermoid cyst is a rare congenital anomaly developed because of dysembryoplasia during the third to fifth week of gestation. We describe the unusual epidermal cyst which originating extradurally in internal protuberance in which causes cerebellar brain abscess. Neurosurgical intervention is advocated to prevent the ongoing risk of significant complications. Meticulous care was taken to grossly excised all the pathologic tissue to avoid recurrence.